2002
DOI: 10.1074/jbc.m202815200
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer-binding Proteins β and δ Mediate the Repression of Gene Transcription of Cartilage-derived Retinoic Acid-sensitive Protein Induced by Interleukin-1β

Abstract: Cartilage-derived retinoic acid-sensitive protein (CD-RAP) is a secreted protein expressed by chondrocytes; the expression is repressed by interleukin 1␤ (IL-1␤). To investigate the transcriptional mechanism, by which CD-RAP expression is suppressed by IL-1␤, deletion constructs of the mouse CD-RAP promoter were transfected into rat chondrocytes treated with or without IL-1␤. The results revealed an IL-1␤-responsive element located between ؊2138 and ؊2068 bp. As this element contains a CAAT/enhancer-binding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
97
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 54 publications
4
97
0
Order By: Relevance
“…C/EBP␤ is known to be induced by pro-inflammatory cytokines such as IL-1␤, IL-6, and TNF-␣, and it is expressed in arthritic cartilage (15,20,22). It has been suggested that C/EBP␤ also plays a role in the repression of COL2A1 in response to inflammatory signals (20). Some other transcription factors including c-Fos, c-Jun, Jun B, and Egr-1, have been reported to be induced by FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C/EBP␤ is known to be induced by pro-inflammatory cytokines such as IL-1␤, IL-6, and TNF-␣, and it is expressed in arthritic cartilage (15,20,22). It has been suggested that C/EBP␤ also plays a role in the repression of COL2A1 in response to inflammatory signals (20). Some other transcription factors including c-Fos, c-Jun, Jun B, and Egr-1, have been reported to be induced by FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, C/EBP␤ (encoded by CEBPB) was first identified as a nuclear protein that bound to the IL-1␤ response element in the IL-6 promoter region (15), and it has subsequently been reported to regulate various genes involved in cell differentiation, proliferation, survival, immune function, tumor invasiveness, and progression (16 -19). Previously, it was reported that C/EBP␤, in response to IL-1␤, down-regulated cartilage-derived retinoic acid-sensitive protein (Cd-rap), a small secreted protein expressed in cartilage throughout chondrogenesis and in mature chondrocytes (20). C/EBP␤ induced by pro-inflammatory cytokines such as IL-1␤ and TNF-␣ directly binds to the MMP13 and MMP3 promoter regions and stimulates their expression in chondrocytes, resulting in degradation of cartilage in arthritis (21,22).…”
mentioning
confidence: 99%
“…IL-1␤ treatment of chondrosarcoma cells increases C/EBP␤ expression, which in turn represses CD-RAP and Col2a1 gene transcription (14). Furthermore, it was recently reported that C/EBP␤ mediates the expression of MMP-1 in cartilage in response to IL-1␤ (25).…”
mentioning
confidence: 97%
“…These pathways lead directly to the deterioration of cartilage matrix structures. IL-1␤ and TNF␣ treatment of chondrocytes induces many transcription factors related to inflammation, such as NF-B, IKK, activator protein 1 (AP-1) (11,12), early growth response 1 (13), and members of the CCAAT/enhancer binding protein (C/EBP) family (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation